2016
DOI: 10.3389/fncel.2016.00131
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Gliosis Interferes with Neurogenesis in Organotypic Hippocampal Slice Cultures

Abstract: Neurogenesis in the adult hippocampus has become an intensively investigated research topic, as it is essential for proper hippocampal function and considered to bear therapeutic potential for the replacement of pathologically lost neurons. On the other hand, neurogenesis itself is frequently affected by CNS insults. To identify processes leading to the disturbance of neurogenesis, we made use of organotypic hippocampal slice cultures (OHSC), which, for unknown reasons, lose their neurogenic potential during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…Similarities in cellular composition and architecture between the in vitro organotypic brain slice cultures and the in vivo setting offer advantages to model complex brain physiology and pathophysiology even though a detailed characterization of the cellular and molecular features of the brain slice culture system was lacking as it pertains to microglia properties in this experimental system. These presumed similarities prompted many studies using variants of the brain slice culture platform to study pathogenic mechanisms involved in stroke, epilepsy, neurodegenerative proteinopathies, and responses to specific neuroinflammatory stimuli (Bernardino, 2005 ; Vinet et al, 2012 ; Ziemka-Nałecz et al, 2013 ; Olajide et al, 2014 ; Hellwig et al, 2015 ; Gerlach et al, 2016 ; Masuch et al, 2016a , b ; Bhatia et al, 2017 ; Saliba et al, 2017 ; Yousif et al, 2018 ; Araki et al, 2019 ; Croft et al, 2019a ; Grabiec et al, 2019 ; Richter et al, 2019 ; Sheppard et al, 2019 ). Revisiting these studies in light of our results may reveal new insights into the role of microglia in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarities in cellular composition and architecture between the in vitro organotypic brain slice cultures and the in vivo setting offer advantages to model complex brain physiology and pathophysiology even though a detailed characterization of the cellular and molecular features of the brain slice culture system was lacking as it pertains to microglia properties in this experimental system. These presumed similarities prompted many studies using variants of the brain slice culture platform to study pathogenic mechanisms involved in stroke, epilepsy, neurodegenerative proteinopathies, and responses to specific neuroinflammatory stimuli (Bernardino, 2005 ; Vinet et al, 2012 ; Ziemka-Nałecz et al, 2013 ; Olajide et al, 2014 ; Hellwig et al, 2015 ; Gerlach et al, 2016 ; Masuch et al, 2016a , b ; Bhatia et al, 2017 ; Saliba et al, 2017 ; Yousif et al, 2018 ; Araki et al, 2019 ; Croft et al, 2019a ; Grabiec et al, 2019 ; Richter et al, 2019 ; Sheppard et al, 2019 ). Revisiting these studies in light of our results may reveal new insights into the role of microglia in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…At DIV 28, DCX expression was limited to fewer cells that were located in the SGZ (Figs 1 and 2), thus revealing neurogenesis in postnatal OTCs. Previous studies have reported a substantial decrease in neurogenesis in OTCs during the first week of cultivation4546. Since DCX expression can persist up to 3 weeks in individual GCs21224849, DCX-positive cells at DIV 28 may represent GCs that were generated at early time points but were still immature and continued to express DCX at the time of fixation.…”
Section: Discussionmentioning
confidence: 93%
“…showed primarily symmetrical division of neuron-committed cells from neural progenitors at DIV 2, thus revealing ongoing neurogenesis at least during the first days in culture 44 . However, with maturation of the cultures the generation of newborn cells subsides 45 46 , making it difficult to use older, i.e. more mature cultures to study adult neurogenesis at later time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is critical to predifferentiate NSCs into OPCs before applying CNTF so as to avoid astrocytic differentiation of NSCs as triggered by CNTF effect 22. Our previous studies focused on using NT‐3 and its receptor TrkC gene modification technique to promote neuronal differentiation of NSCs with synaptic transmission capability 11, 23.…”
Section: Discussionmentioning
confidence: 99%